A educação da imaginação por meio da literatura - Fonseca Júnior, Fábio da (2019)
The theme of this dissertation is to understand how the imaginary formed through literature can contribute to the ethical and aesthetic education of the subject. I understand that imagination plays a crucial role in understanding and developing the human being's ability to know and think. To this end, it will be necessary to understand the philosophical aspects that make the debate on the education of imagination relevant to the context of education; revealing the importance of imagination, what is its role in understanding reality and how fantasy literature can contribute to the constitution of the imaginal world. To then, Identify how imagination plays a fundamental role in understanding the world and how literature can contribute to the ability to understand reality and the moral formation of the subject; and with this, understanding how the education of the imagination, through literature, can increase the ability to understand reality and how it can be absorbed by formal education. In order to achieve these goals, the first chapter will identify how imagination plays an indispensable role in understanding the world and how literature can contribute to the understanding of reality and the moral formation of the subject. Evidencing this aspect, the second chapter will show how the Homeric literature had an enormous importance for the development of the Greek civilization, being the first reference model of values for the formation of that people. For then, in the last chapter demonstrate how the arts of Belo and literature have a crucial role in the constitution of the human understanding, contributing for the human being to fulfill its ontological purpose, besides, it will be demonstrated how the literature can enlarge the capacity of understanding of reality and how this can be absorbed by formal education, using the various literary genres to deepen understanding at various levels of reading. The stimulus to produce this research comes from my experience as a teacher, because in teaching philosophy in high school and elementary school I realized that students had an understanding far beyond what was necessary to understand the abstract discourse proper to philosophical language. The relevance of the research will be whereas the education of imagination through literature aims to enable the subject to progressively develop the basic elements of human cognition and its moral structure, which will enable the correct widening of the cognitive capacities of the subject. . This research has a qualitative character, and was developed through bibliographic research and done in essay form. A number of authors from the philosophical tradition and education were used, but among them we can highlight Aristotle, Northop Frye, and Mortimer Adler.